(untitled) (Journal of the College of Basic Education, 2026)
The purpose of the study was to investigate the biofilms formation of some environmental and clinical pseudomonas aeruginosa and their resistance to common antibiotics. In this study, 55 environmental water samples were collected between 13th till 30th January 2023 , from Al-Aobur water treatment station of Al-Baladiyat in middle of Baghdad, the old Rostumia project for sewage treatment of Diyala Bridge in eastern of Baghdad, and Central oil company in northern of Baghdad. Bacterial isolates were obtained and identified using standard diagnostic methods. From 700 environmental isolates were recovered, 102(14.6%) was Pseudomonas spp. At the same time, 130 clinical isolates of bacteria were collected in the baghdad hospitals including, Ghazi Al-Hariri Hospital, Al-Karkh General Hospital, Medical City Teaching laboratories and Al-Yarmouk teaching hospital. There were burns, wounds, blood, sputum, urine and pus as clinical sources. The clinical isolates collected between January and February 2023, were Gram-negative non-lactose fermenters, comprising 54 (41.5%) Pseudomonas spp. Genetic identification using 16S rRNA confirmed 52 (51%) of the environmental Pseudomonas spp. isolates as P. aeruginosa, Similarly, among the clinical isolates, 27(50%) were confirmed as P. aeruginosa. The environmental and clinical P. aeruginosa isolates were tested in regard to antibiotic susceptibility which showed high sensitivity in the environmental isolates. The level of resistance was greater with clinical P. aeruginosa isolates. The production of biofilm was established through Congo Red Agar (CRA) and Microtiter Plate (MTP). Among environmental isolates, 34 (65.4%) were biofilm-positive using CRA, while 18 (34.6%) were negative. For clinical isolates,12 (44.4%) positive,15 (55.6%) negative. In MTP method, strong biofilm formation was observed in 34(65.4%) environmental isolates, moderate 17(32.7%), and weak 1(1.9%). Among clinical isolates, strong biofilm formation was 4(14.8%), moderate 10(37%), and weak 13(48.2%). Pseudomonas aeruginosa, were constituted the largest proportion of other Pseudomonas spp isolated from environmental and clinical samples . Antibiotic susceptibility testing revealed high sensitivity among environmental isolates. Clinical isolates exhibited higher resistance levels. Environmental isolates were more productive biofilm, compare with clinical isolates.